N'ZAS CHOC / Nazianiwati Othman ... [et al.] - Othman, Azianiwati; Sarriffulddin, Zuraidah; Ibrahim, Anwar; Mohd Sarip, Safrib (Faculty of Information Management, 2002)
Our company's name is N'ZAS Choc'. The type of our business is partnership. Our partners in this business are Nazianiwati othman, Safri Mohd Sarip, Anwar Ibrahim, and Zuraidah Sarriffulddin. The position in this business are Nazianiwati othman as a Administration Executive, Safri Mohd Sarip as a Financial Executive, Anwar Ibrahim as a Marketing Executive, and Zuraidah Sarriffulddin as a Operation Executive. We are agreed to run the business in manufacturing chocolate and operating chocolate shop. We choose this business because the demand of the chocolate is higher. The majority of demand comes from children and teenagers. Besides that, some of celebration likes Valentine Day, Chinese New Year, Mother Day and other. We are providing chocolate that we make, candies and cookies. Cookies and candies we get from supplier. Our shop at Mid Valley MegaMall, Kuala Lumpur. One of the driving factor is at Mid Valley did not have more competition. Based on our research, chocolate shop at Mid Valley just two or three shop only. So we choose the correct place to sell our product. Our manufacturing factory is in Petaling Jaya, Selangor.